Legal and Technological Aspects of Cybersecurity and Cyber Resilience in Facing Global Cyber Threats - Hassanain Haykal (Jurnal Restorasi : Hukum dan Politik, 2026)
The emergence of artificial intelligence has shifted cybercrime patterns in Indonesia from manual to automated and adaptive attacks. Deepfakes, adversarial machine learning, and automated social engineering have become powerful tools that can exploit vulnerabilities in computer systems, algorithms, and data in cyberspace. These threats pose significant dangers to critical sectors, particularly banking and digital public services, due to potential economic losses, data breaches, and violations of public privacy. This paper will focus on issues related to cybersecurity and cyber resilience from a legal and technological perspective in the face of global cyber threats. The methodology applied in this research includes normative juridical research using principles of law, systematic law, synchronous law, and comparative law. The results show that Indonesia has attempted to adapt to the country's legal structure through the enactment of Law No. 1 of 2024 on Information and Communication Technology (ITE), Law No. 27 of 2022 on Personal Data Protection (PDP), and the New Criminal Code No. 20 of 2025, which considers AI as an electronic agent. However, issues remain regarding digital evidence methods and changes in procedural law regarding autonomous AI agents. Traditional cybersecurity measures will not be able to combat AI attacks. Therefore, an integrated cybersecurity approach will be needed to protect against AI threats. This integrated cybersecurity approach will require the ratification of the Cybersecurity and Cyber ​​Resilience Bill as an umbrella law to align PDP and ITE. Furthermore, this cybersecurity approach must include adaptive risk management, mandatory reporting to the BSSN (National Agency for the Protection of Information and Communications), SPBE audits, cybersecurity workforce development, a Pentahelix approach, and national data sovereignty.